2010
DOI: 10.1016/j.seizure.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Anterior striatum with dysmorphic neurons associated with the epileptogenesis of focal cortical dysplasia

Abstract: The epileptogenesis of the striatum is unknown. We describe the case of a 12-year-old girl with intractable epilepsy who was treated by surgical interventions. Magnetic resonance imaging (MRI) showed ambiguous corticomedullary boundary in the left frontal lobe, and magnetoencephalography (MEG) revealed spike dipoles in the vicinity of the left ventral striatum. The epileptic seizures disappeared after partial resection of the frontal lobe, but recurred within 2 months and remained intractable. Neuropathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…Notably, the basal ganglia imaging changes seemingly correlated with seizure burden at the time. There were histopathological features suggestive of dysplasia, consistent with previous reports of dysmorphic neurons in the basal ganglia of patients with FCD 6,7 . Deep sequencing revealed somatic MTOR mosaicism in both the basal ganglia and overlying cortex.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Notably, the basal ganglia imaging changes seemingly correlated with seizure burden at the time. There were histopathological features suggestive of dysplasia, consistent with previous reports of dysmorphic neurons in the basal ganglia of patients with FCD 6,7 . Deep sequencing revealed somatic MTOR mosaicism in both the basal ganglia and overlying cortex.…”
Section: Discussionsupporting
confidence: 88%
“…Given the mounting evidence for epileptogenicity of dysmorphic neurons in FCD and tuberous sclerosis complex, 16,17 it is conceivable that the dysmorphic neurons in our patient's dysplastic basal ganglia could play an active role in seizure generation. This notion is supported by previous reports of successful seizure control following the resection of basal ganglia structures in patients with FCD who had ongoing seizures despite the removal of cortical lesions 6,7 . Although the underlying genetic basis for these patients is not known, histopathological examination of the resected basal ganglia showed dysmorphic neurons, demonstrating that dysplasia of the basal ganglia can occur in patients with FCD and may contribute to seizure generation 6,7 …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, it may be based on the imbalance between the excitatory and inhibitory neuronal circuits, which seems to play an important role in the initiation and spread of epileptic seizures [8]. It is of considerable interest that the basal ganglia with dysmorphic neuron of FCD have been associated with epileptogenesis [9]. Recently, we reported that deep structure resection improved seizure control and resulted in no motor deficit after operation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…12 Several case reports suggest that abnormalities of deep brain structures may play a critical role in epileptogenesis. 13,14 In the present study, we investigated whether subcortical cerebral infarctions (i.e., lacunar infarcts or BAD individually) can increase the prevalence of epileptic seizures in Japanese patients. We also evaluated whether risk factors for seizures and involvement of the basal ganglia or thalamus could be related to seizures.…”
Section: Introductionmentioning
confidence: 99%